2021
DOI: 10.12659/msm.933830
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus Flavone Induces Proliferation and Differentiation of Neural Stem Cells in a Cerebral Infarction Model

Abstract: Background Ischemic cerebrovascular disease leads to the activation and differentiation of neural stem cells (NSCs) into mature neurons and glia cells to repair nerve damage. Astragalus flavone (ASF) has shown its potential role in proliferation and differentiation into dopamine neurons of NSCs. Material/Methods Cerebral infarction models were constructed to determine the effects of ASF on NSCs in vivo and in vitro. Results ASF therapy had th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…ASF, a flavonoid, was administered to rats exposed to focal cerebral ischemia at doses of 2.5, 5, and 7.5 mg/kg for 7 and 14 days. ASF treatment improved neurological functions and increased the proliferation of neural stem/progenitor cells after cerebral ischemia (Gao et al, 2022b ). In Medline searches, only one study was found determining the effect of naringin treatment on neurogenesis (Yang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…ASF, a flavonoid, was administered to rats exposed to focal cerebral ischemia at doses of 2.5, 5, and 7.5 mg/kg for 7 and 14 days. ASF treatment improved neurological functions and increased the proliferation of neural stem/progenitor cells after cerebral ischemia (Gao et al, 2022b ). In Medline searches, only one study was found determining the effect of naringin treatment on neurogenesis (Yang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies have shown that the these flavonoids have similar effects to calycosin, quercetin. In addition, they are known to promote neurogenesis after ischemic stroke ( Gao and Li, 2018 ), but which of them is playing this role is unclear. Therefore, their therapeutic effects are not elucidated here in detail.…”
Section: Potential Mechanisms Underlying the Therapeutic Effect Of Bi...mentioning
confidence: 99%
“…Similarly, Astragalus and its active components affect neurogenesis through MGB axis immune pathways, which may be related to microglia activation ( Li et al., 2020 ), but the specific mechanism needs to be further confirmed. In vitro , Astragaloside VI promotes the differentiation of primary NSCs into neurons and astrocytes, similarly to Astragalus flavor, which up-regulated Notch1 , Jagged1 , Mash1 , Ngn1 , and Ngn2 expression in NSCs ( Gao et al., 2022 ). Epigallo-catechin-3-gallate (EGCG), the main component of Camellia sinensis (green tea), increases the abundance of Bacteroides uniformis , Bacteroides vulgatus , Bacteroides stercoris , Bacteroides thetaiotaomicron , and Bacteroides cellulosilyticus in human gut microbiota ( Liu Z. et al., 2020 ).…”
Section: Traditional Chinese Medicine Can Affect Neurogenesis By Regu...mentioning
confidence: 99%